Perlindungan Hukum Terhadap Konsumen Atas Jaminan Produk Halal Pada Makanan Dan Minuman UMKM di Kota Bekasi - Ahmad Baihaki; Rabiah Al Adawiah; Naffa Rizky Hermawati (KRTHA BHAYANGKARA, 2022)
Guarantees for halal products in Indonesia are mandated by Law Number 33 of 2014 concerning Halal Product Guarantee which stipulates that every product that enters, circulates, and is traded in Indonesia must be guaranteed halal. Even according to Law Number 11 of 2020 concerning Job Creation, the obligation to fulfill halal product guarantees also applies to Micro, Small and Medium Enterprises (UMKM). This research uses a normative and empirical legal research method that seeks to examine and analyze the laws and regulations regarding halal product guarantees and the implementation of these laws on UMKM businessman in Bekasi City. Based on the results of the study, the laws and regulations regarding the guarantee of halal products have provided legal certainty for consumers. However, in implementation, the regulation has not been effective, it is proven that there are still many food and beverage products produced by UMKM in Bekasi City that do not have a halal certificate. This is due to many factors, including the relationship between the Halal Product Assurance Agency (BPJPH) with the Halal Inspection Agency (LPH) and the Indonesian Ulema Council (MUI) and related ministry institutions that have not been maximized, thus hampering the implementation of halal product guarantees. In addition, the lack of legal awareness for UMKM businessman about the importance of guaranteeing halal products has caused the rules regarding the obligation to guarantee halal products to have not been implemented optimally.